In Search of Studies on Education during the Monarchical Period referenced within Gramscian Historicism - Rodrigues de Sousa, André Wagner; Salvatti Coutinho, Luciana Cristina (International Gramsci Journal, 2025)
The article with the paths taken to locate gramscian studies of education that focus on objects of analysis dating from the imperial period of brazilian history. By recognizing the centrality of historicism in the development of the philosophy of the praxis, the work aims to identify, among the academic research in the educacional field referecend in Antonio Gramsci’s theoretical contribution, which were guided from a historical perspective, focusing their analyzes on objects located in the 19th century. Through bibliographical research, the study synthetically presents the reception of the sardinian philosopher’s work in the national territory and deals with some important studies that set out to gather and analyze gramsciam production in Brazil in recents decades. In the final considerations, after examining the data gathered, some hypoteses are made that can help to understand the phenomenon revealed by the exploratory research.